Employee Sensemaking on the Importance of Sustainability Reporting in Sustainability Identity Change - Tiina Onkila; Marileena Mäkelä; Marko Järvenpää (Wiley, 2022)
This study examines employee sensemaking processes in order to understand the role of sustainability
reporting in organizational identity change. Through an analysis of 52 interviews with employees
in two Finnish companies, we develop sensemaking frames for understanding the role of
sustainability reporting in organizational identity change. The three sensemaking frames are individualistic,
relational and decoupled. Each of these sensemaking frames differs in stakeholder
orientation. They indicate that sensemaking influences the interpretation of how important sustainability
reporting is for organizational identity change towards sustainability. The study shows
how the individualistic and relational frames serve as sensemaking frames for framing sustainability
reporting as being possibly beneficial in organizational identity change. However, the
decoupled frame highlights the deficiencies of reporting, especially from the perspective of a collectivistic
stakeholder orientation. We propose that a better understanding of the decoupled
sensemaking frame helps to understand the justifications for the increasing criticism that has
been targeted at sustainability reporting.